1999
DOI: 10.1016/s0014-5793(99)00662-6
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of a conserved tetraloop in the 5′ untranslated region of hepatitis C virus identifies a novel RNA element essential for the internal ribosome entry site function

Abstract: The 5P P untranslated region of hepatitis C virus RNA forms an extensive secondary structure including several hairpin motifs and mediates translation initiation by an internal ribosome entry site-dependent pathway. We report, here, an extensive mutagenesis analysis of a highly conserved tetraloop in the 5P P untranslated region of hepatitis C virus, namely hairpin IIIe (295P P-GAUA-298P P). Our results demonstrate that hairpin IIIe is essential for the internal ribosome entry site function. Moreover, they ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 39 publications
(71 reference statements)
2
48
0
1
Order By: Relevance
“…Studies on domain IIIe of the HCV IRES element have indicated that each of the nucleotides within the highly conserved GAUA tetraloop is crucial for HCV IRES activity (22,31). This domain, together with domain IIId, plays an essential role in binding the 40S ribosomal subunit (18,25,39).…”
Section: Resultsmentioning
confidence: 99%
“…Studies on domain IIIe of the HCV IRES element have indicated that each of the nucleotides within the highly conserved GAUA tetraloop is crucial for HCV IRES activity (22,31). This domain, together with domain IIId, plays an essential role in binding the 40S ribosomal subunit (18,25,39).…”
Section: Resultsmentioning
confidence: 99%
“…In patient A, two brain-derived sequences (B4 and B23) showed marked reductions in IRES function compared to the consensus sequence (translational activity for B4 ϭ 5%, and translational activity for B23 ϭ 53% [P Ͻ 0.001]). B4 contained two mutations (C to U at position 122 and A to G at position 298), both of which have been shown by mutagenesis to lie in sequence motifs (pyrII and the domain IIIe tetraloop, respectively), which are crucial to IRES function (46,57). Similarly, the single mutation in B23 (U to C at position 259) falls within the domain IIId loop E motif, a highly conserved region, in which mutations are deleterious to IRES function (20).…”
Section: Resultsmentioning
confidence: 99%
“…In patient A, it is interesting that the mutations segregate along the IRES, with the brain sequence mutations all found in domains III and IV, specifically within the pyrII motif, the domain IIIe tetraloop, and the domain IIId loop E motif, which are crucial to IRES function (20,46,57), in addition to the A204, A243 mutation (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…This IRES shares many characteristics with the HCV IRES, including the presence of a pseudoknot (domain IIIf) and a highly conserved stem-loop (domain IIIe), which plays a critical role in the interaction with the 40S ribosomal subunit (Psaridi et al 1999;Lukavsky et al 2000;Kieft et al 2001;Laletina et al 2006). We have now constructed a series of plasmids containing some of these variants of the PTV-1 IRES; the cDNA (z300 nt) was inserted as a BamHI fragment into the pRBRluc vector (Fig.…”
Section: Defective Ptv Ires Elements Do Not Inhibit Translation Of Momentioning
confidence: 99%